Phytochemical and Antibacterial Activity of Aloe vera, Camellia sinensis and Momordica charantia - Shahzadi, Tahreem; zahoor, sana; Arooba; Afzal, Omama (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
Traditional medicines, largely derived from plants, contain bioactive compounds that serve as protective agents against environmental stressors (biotic and abiotic) and can also enhance human health. With the alarming rise in antimicrobial resistance, there is an urgent need to explore safe and effective plant-derived alternatives to synthetic antibiotics. The present study was therefore designed to evaluate the phytochemical composition and antibacterial potential of three commonly used medicinal plants: Camellia sinensis, Aloe vera, and Momordica charantia. Aqueous and ethanolic extracts were prepared and qualitatively screened for tannins, alkaloids, saponins, flavonoids, steroids, proteins, carbohydrates, phlobatannins, and terpenoids. Quantitative analysis further revealed that M. charantia had the highest alkaloid content (5.29%), while its ethanolic extract exhibited the greatest protein (37.9 mg/g dry extract) and carbohydrate levels (30.6 mg/g dry extract). The antibacterial activity of the extracts was tested against a Gram-positive strain (Staphylococcus aureus) and a Gram-negative strain (Klebsiella pneumoniae). The results showed that C. sinensis consistently demonstrated the strongest antibacterial activity in both aqueous and ethanolic extracts, producing inhibition zones of 20 ± 0.95 mm against S. aureus and 12 ± 2 mm against K. pneumoniae. In comparison, M. charantia exhibited selective inhibition, being effective only against S. aureus, while A. vera showed moderate antibacterial activity depending on the extraction solvent. Overall, the findings highlight the therapeutic promise of C. sinensis as a natural antimicrobial agent. Future studies should expand antimicrobial screening to additional pathogens and include in vivo assays to validate the clinical applicability of these extracts.